2020
DOI: 10.1002/aorn.13271
|View full text |Cite
|
Sign up to set email alerts
|

State of the Science: A Concept Analysis of Surgical Smoke

Abstract: Surgical smoke has not been clearly defined in the literature and often is identified using surrogate terms (eg, plume). In January 2020, a literature search was performed and a principle‐based concept analysis involving four general principles (epistemological, pragmatic, linguistic, and logical) was used to define surgical smoke and identify implications for perioperative personnel, patients, researchers, and policymakers. Surgical smoke is a visible plume of aerosolized combustion byproducts produced by hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…As an advanced surgical instrument, ultrasonic scalpel can be used in various soft tissue anatomical operations [1][2][3] . Compared with traditional scalpels, ultrasonic scalpels have higher cutting accuracy, less release of toxic surgical smoke [4] , and can reduce the probability of safety hazards such as implanted electronic device failures [5] . Therefore, relevant scholars have conducted a lot of research on ultrasonic scalpel.…”
Section: Introductionmentioning
confidence: 99%
“…As an advanced surgical instrument, ultrasonic scalpel can be used in various soft tissue anatomical operations [1][2][3] . Compared with traditional scalpels, ultrasonic scalpels have higher cutting accuracy, less release of toxic surgical smoke [4] , and can reduce the probability of safety hazards such as implanted electronic device failures [5] . Therefore, relevant scholars have conducted a lot of research on ultrasonic scalpel.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the National Institute for Occupational Safety and Health (2017) has proposed local exhaust ventilation in the OR as a method for the immediate elimination of surgical smoke. Despite such proposals, only two states in the United States -Rhode Island and Coloradohave laws requiring surgical smoke control and mitigation, while nine other states (Georgia, Oregon, Tennessee, Illinois, Iowa, Kentucky, Utah, Connecticut, and New Jersey) are currently introducing similar legislation (Vortman et al, 2021). These acts require all state-licensed hospitals and ambulatory surgery centers to use smoke evacuation systems during procedures that generate surgical smoke.…”
Section: Introductionmentioning
confidence: 99%
“…The remainder is particulate matter that can contain blood fragments, bacteria, viruses, viable cancer cells, and gases that are known carcinogens, teratogens, and mutagens such as benzene, toluene, acetylene, xylene, and hydrogen cyanide. 1,3 Experimental evidence has also shown that surgical smoke can carry human coronavirus RNA, suggesting a possibility that SARS-CoV-2 (COVID-19) could also be present; 4 however, at the time of writing there is no evidence of transmission.…”
mentioning
confidence: 99%